Life Stage‐ and Sex‐Specific Sensitivity to Nutritional Stress in a Holometabolous Insect - Leon Brueggemann; Pragya Singh; Caroline Müller (Ecology and Evolution)
ABSTRACT Over lifetime, organisms can be repeatedly exposed to stress, shaping their phenotype. At certain, so‐called sensitive phases, individuals might be more receptive to such stress, for example, nutritional stress. However, little is known about how plastic responses differ between individuals experiencing nutritional stress early versus later in life or repeatedly, particularly in species with distinct ontogenetic niches. Moreover, there may be sex‐specific differences due to distinct physiology. Larvae of the holometabolous turnip sawfly, Athalia rosae, consume leaves and flowers, while the adults take up nectar. We examined the effects of starvation experienced at different life stages on life‐history, adult behavioural and metabolic traits to determine which stage may be more sensitive and how specific these traits respond. We exposed individuals to four nutritional regimes, either no, larval, adult starvation or starvation periods as larvae and adults. Larvae exposed to starvation had a prolonged development, and starved females reached a lower initial adult body mass than non‐starved individuals. Males did not differ in initial adult body mass regardless of larval starvation, suggesting the ability to conform well to poor nutritional conditions. Adult behavioural activity was not significantly impacted by larval or adult starvation. Individuals starved as larvae had similar carbohydrate and lipid (i.e., fatty acid) contents as non‐starved individuals, potentially due to building up energy reserves during development, while starvation during adulthood or at both stages led to reduced energy reserves in males. This study indicates that the sensitivity of a life stage to stress depends on the specific trait under consideration. Life‐history traits were mainly affected by larval stress, while activity appeared to be more robust and metabolism mostly impacted by the adult conditions. Individuals differed in their ability to conform to the given environment, with the responses being life stage‐ and sex‐specific.